Creating community learning for empowerment groups: an innovative model for participatory research partnerships with refugee communities - Yohani, Sophie; Kirova, Anna; Georgis, Rebecca; Gokiert, Rebecca; Taylor, Mischa; Tahir, Sabah (Frontiers in Education, 2023)
Empowering communities to respond to humanitarian crises is one of the core principles of the United Nations High Commission for Refugees. In response to large numbers of refugees resettling in Canada from Syria as they fled its civil war, a community-based research partnership was initiated to examine the psychosocial needs and adaptation processes of Syrian individuals and families. In this article, we introduce Community Learning for Empowerment Groups (CLEGs) as a methodological innovation in participatory research partnerships and demonstrate how they can be used to harvest local knowledge and create critical spaces for transformative learning. We describe the process of co-creating CLEGs with seven recently resettled Syrian community leaders, examples of their implementation, and lessons learned in our community-based participatory research (CBPR). Grounded in a transformative paradigm, our CBPR project occurred over three phases of implementation. Activities undertaken by the research team in phase one aimed at empowering the leaders through a “train-the trainer” and collaborative learning approach to lead CLEGs in phase two. Focus groups were held with leaders in phase two to explore their experiences leading CLEGs. Discussions in focus groups revealed that leaders were empowered to adapt their learning from phase one according to their group dynamics and personal leadership style. Deepened insights and new facilitation approaches were evidence of leaders’ growth, as exemplified in the focus groups. Leaders were able to support their groups to generate and, in some cases, implement community-based solutions to their groups’ psychosocial challenges. Community Learning for Empowerment Groups are a promising model for supporting power sharing and knowledge co-construction in participatory research partnerships.